Economic, Entrepreneurial and HR Insights in Professional Training and Adult Education - Megyesi Csilla (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-«RIK-U» Kiadó, 2016)
Abstract. The economic competitiveness of a country largely depends on the society’s financial culture, and the social image of the enterprises. In Hungary we are not really good in the field of financial literacy and of entrepreneurial prestige, either. It is reasonable to seek the causes partly in the economic and entrepreneurial training, and the present study set this goal.

Egy ország gazdasági versenyképessége nagyban függ attól, hogy milyen a társadalma pénzügyi kultúrája, és milyen a vállalkozások társadalmi megítélése. Magyarországon sem az alapvető pénzügyi ismeretek, sem a vállalkozói presztízs terén nem állunk igazán jól. Az okokat indokolt részben a gazdasági és vállalkozási ismeretek oktatásában keresni – jelen tanulmány is ezt tűzte ki célul.
https://kmf.uz.ua/wp-content/uploads/2017/03/Limes2016_netre.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006463
Keywords: economic competitiveness; Financial Training; Economic; Adult Education